THE EFFECTIVENESS OF THE SIKS-NG APPLICATION IN POVERTY DATA MANAGEMENT - Putri, Sabrina Aisah; Balahmar, Ahmad Riyadh Umar (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: The goal of this study is to evaluate how well the Next Generation Social Welfare Information System (SIKS-NG) is working in managing poverty data in Sumput Village, Sidoarjo District. The research used a qualitative descriptive approach, involving observations, interviews, and document analysis at the study location. This method was based on the theory of program effectiveness as outlined by Budiani (2007). Results: The results of the study indicate that the implementation of SIKS-NG in Sumput Village has not been fully optimized, based on indicators of target accuracy, socialization, monitoring, and program goal achievement. The main challenges include insufficient field verification, low community understanding, and inadequate infrastructure. The uniqueness of this study lies in its focus on analyzing the effectiveness of the social data management information system at the village level in a specific and comprehensive manner, as well as comparing the findings in Sumput Village with previous studies in other areas. Novelty: This research provides an important contribution to the development of strategies to improve the implementation of digital-based social information systems at the village level to support improved data accuracy and the effectiveness of social assistance distribution.